2018
DOI: 10.1016/j.nicl.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Does the late positive component reflect successful reading acquisition? A longitudinal ERP study

Abstract: Developmental dyslexia is a reading disorder that is associated with deficits in phonological processing, where the exact neural basis for those processing deficits remains unclear. In particular, disagreement exists whether degraded phonological representations or an impaired access to the phonological representations causes these deficits. To investigate this question and to trace changes in neurophysiology during the process of reading acquisition, we designed a longitudinal study with event related potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…These results suggest that the access to phonological representations of words may be impaired and/or that phonological representations may be underspecified [ 19 ] in dyslexic individuals. This hypothesis was later supported by Wachinger et al [ 31 ], who used a word processing task in a longitudinal study with German children between kindergarten and second grade. In this task, children were asked to read a word or look at a picture (control condition) and to decide whether it matched an acoustically presented word.…”
Section: Erp Recordings In the Dyslexic Populationmentioning
confidence: 73%
See 1 more Smart Citation
“…These results suggest that the access to phonological representations of words may be impaired and/or that phonological representations may be underspecified [ 19 ] in dyslexic individuals. This hypothesis was later supported by Wachinger et al [ 31 ], who used a word processing task in a longitudinal study with German children between kindergarten and second grade. In this task, children were asked to read a word or look at a picture (control condition) and to decide whether it matched an acoustically presented word.…”
Section: Erp Recordings In the Dyslexic Populationmentioning
confidence: 73%
“…In addition, Hasko et al [ 19 ] surmised that LPC might reflect access to the phonological lexicon. With respect to dyslexia, reduced LPC amplitudes have been found in dyslexic adults [ 43 ], adolescents [ 30 ] and children [ 19 , 31 ]. For example, and as far as word recognition memory is concerned, Schulte-Körne et al [ 30 ] used a recognition paradigm with previously presented pseudowords and symbols in ten-year-old dyslexic children; in this task, participants had to study a list of pseudowords and symbol strings and then decide whether the presented stimulus had already been seen.…”
Section: Erp Recordings In the Dyslexic Populationmentioning
confidence: 99%
“…This seems to suggest delayed visual specialization maxima in dyslexic readers. In relation to phonological processing, another study 46 reported attenuated LPC amplitudes in children with dyslexia compared to typical readers. Interestingly, those effects were confined to word stimuli (in contrast to pictures) and temporo-parietal electrode sites.…”
Section: Development Of the Reading Network In Dyslexiamentioning
confidence: 99%
“…Audiovisual integration was also examined in a longitudinal ERP study, which followed children across five time points from kindergarten to the end of the second grade 46 . The analysis focused on a late positive component (LPC) over the temporo-parietal scalp electrodes elicited by an explicit reading task, where congruent or incongruent audiovisual pairs were presented with either words or pictures.…”
Section: Typical Reading Developmentmentioning
confidence: 99%
“…ERPs allow a very precise temporal tracking of the electrocortical brain activity, which in turn allows high sensitivity to the rapid information processing stream. Given their use to track cognitive processes in longitudinal (Fruehwirt et al, 2018; Wachinger et al, 2018) or clinical studies (Houston & Schlienz, 2018; Morand-Beaulieu et al, 2018), the test-retest reliability of ERPs must be established. Test-retest reliability refers to the consistency of a measure or an instrument over time.…”
mentioning
confidence: 99%